The more the better? How collateral levels affect credit risk in agricultural microfinance - Kirsten Müller; Oliver Musshoff; Ron Weber (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2014)
Financial institutions still neglect to address agricultural clients. The main reasons for that are their perception that farmers bear higher risks than non-farmers and that their loan products are inadequate to accommodate the needs of agricultural entrepreneurs. As a result, many farmers still lack access to external finance. The aim of this paper is to investigate determinants of credit risk for agricultural loans disbursed by a Microfinance Institution (MFI) in Azerbaijan. In this context special attention is paid to repayment flexibility and the role of collaterals. MFIs are among the first financial institutions recently focusing on farmers with new loan products. We find that farmers are less risky than non-farmers, which is surprising because the opposite is widely believed. We furthermore find that the level of collateral has a negative influence on credit risk. Beyond that, we find that repayment flexibility increases credit risk.
Keywords: Q12; Q14; 330; microfinance; collaterals; Tobit Model; credit risk; small-scale farmer